Radio Opacity of Honey: A Unique Physical Property with The Potential of A Radio Contrast Media - Faruq, Mohammad Omar; Mokarim, Abul; Mursalin, Rafael; Susan, Md Abu Bin Hasan; Ahmed, Saika; Choudhury, Ashiq Haider; Ara, Gulshan; Faruq, Ridwan Naim; Habib, Samira Humaira; Karim, Md Rezaul; et al. (Bangladesh Critical Care Journal, 2018)
Background: Honey is known for its various physical properties, chemical contents and as a topical therapeutic agent. However its potential use in diagnostic radiology has not been reported. Aims: To establish radio opacity of honey as its unique physical property, to establish its relationship with other physical properties, chemical contents and to determine if honey has any potential as diagnostic contrast media. Material and Methods: CT scanner was used to calculate radio density in Hounsfield Unit (HU) on six honey samples, honey samples of different dilutions, Iopamidol, 25% glucose and agents containing Calcium, Iron, Magnesium and Potassium. Plain X-ray was obtained on honey samples, honey filled plastic tubes, and honey impregnated cotton gauze. Radio density of honey samples was compared with four selected physical properties of honey. Results: Radio density of six honey samples ranged between 287±3.4 HU and 329±5.3 HU. Radio density of 2% Iopamidol, a commonly used radio contrast agent was 341±8.2 HU. Compared to honey, 25% glucose had low radio density and 15% Potassium chloride had high radio density. Radio density of six honey samples were compared with corresponding density (p=0.0003), specific gravity (p=0.0002), refractive index (p=0.0001) and dynamic viscosity (p=0.10). Plain X-ray images of honey samples showed marked radio opacity. Conclusion: Radio opacity of honey is probably related to its high carbohydrate and potassium content. Honey’s anti-bacterial & healing benefit will offer dual therapeutic and diagnostic advantage with concomitant use as a topical radio contrast agent. Bangladesh Crit Care J September 2018; 6(2): 95-99